(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2018)
The review systematizes and analyzes the literature data (100 sources) regarding the recyclization of 3-arylisocoumarins (3-aryl-1H-isochromen-1-ones) under the action of primary N-nucleophiles that leads to the formation of 3-arylisoquinolones (3-arylisoquinolin-1(2H)-ones). This reaction may be carried out with a wide range of primary aminogroup-containing compounds: ammonia, primary aliphatic, aromatic, and heteroaromatic amines, hydrazine, and hydroxylamine. This transformation is not hindered by the presence of active functional groups (hydroxyl, acetal, carboxyl, ester, nitrile groups, or additional aminogroup) neither in 3-arylcoumarin nor in the primary amine. A special attention has been paid to reaction conditions (temperature regime, duration, solvent, catalysts), which may vary greatly. In particular, it is pointed out that in most cases to carry out high-temperature recyclization of 3-arylisocoumarins with ammonia and volatile amines with low molecular weight the use of closed reactors and high-pressure flasks was required. The cases of successful recyclization of 11,12-dihydrodibenzo[c,h]chromen-6-ones, indeno[1,2-c]isochromen-5(11H)-ones, isochromeno[4,3-c]chromen-6,11-dione and 5H-benzofuro[3,2-c]isochromen-5-one are reviewed separately. The polycondensated heterocyclic system of these compounds contains a 3-arylisocoumarin fragment. The biological activity data is presented for the compounds obtained via this transformation – 3-arylisoquinolin-1(2H)-ones, and also polycondensated systems that contain this fragment, e.g. 11,12-dihydrobenzo[c]phenanthridin-6(5H)-ones and 6H-indeno[1,2-c]isoquinoline-5,11-diones. The opportunities to use 3-arylisoquinolin-1(2H)-ones in the synthesis of other compounds of isoquinoline family, e.g. natural benzo[c]phenanthridinealocoloids, are demonstrated.